PENGARUSUTAMAAN GENDER DALAM PENANGGULANGAN KEMISKINAN - Ahmad Muttaqin (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
Poverty is a crucial problem for every nation that not only affects to the failure of fulfilling the basic rights of people to live indignity but also reinforce unjust practices. One of the unjust forms in poverty is gender. Social burden in each poverty dimension includingeconomic, social, cultural, and political structural dimensions is borne disproportionately by men and women. Women groups bear theburden of the social impact of poverty much higher than men. This condition is further exacerbated by the initiation of intervention in order toreduce the obstacles of poverty which is more projected on a particular group. As a social construction, the difference in gender has beenproved by the contribution to social injustice not only for women but also for men. This gender difference becomes a source of injustice formen and women in their families, society, and state. In advance stage, this may justify gender bias in the systems of distributing authority,division of labor, ownership, and distribution resource. Therefore, the changing gender construction is an urgent need. This context becomesthe intersection between poverty and gender inequality as a perspective to analyze national problem. The program which is designed toreduce poverty is not only oriented to overcome the obstacles of poverty in its various dimensions, but also to transform gender constructionwhich can represent equality and justice